Penerapan Reward and Punishment untuk Meningkatkan Kemampuan Penyelesaian Soal Tes Kemampuan Akademik - Wartinah, Wartinah; Indri Hastuti; Sri Lestari; Hufron Rifa'i; Muh. Farid Yuniarto; Aziz Miftahudin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the application of Reward and Punishment in improving students' ability to complete academic ability test questions and identify the components that determine its effectiveness. This study was conducted at Madrasah Aliyah Negeri 2 Boyolali with a qualitative approach through interview, observation, and documentation techniques. The results of the study indicate that there are four main steps in the application of Reward and Punishment, namely: (1) setting clear goals and criteria so that students understand the academic achievement targets specifically and measurably; (2) positive reinforcement through rewards, such as praise, recognition, or awards that are relevant to students' efforts and achievements; (3) providing constructive punishment, in the form of educational consequences oriented towards improving behavior and increasing abilities, without demeaning students' self-esteem; and (4) evaluating and adjusting the Reward and Punishment system through monitoring test results and students' learning behavior to ensure the effectiveness of the strategies implemented. In addition, four main factors were found that influence the effectiveness of Reward and Punishment, namely: (1) student involvement and motivation in learning; (2) the types and forms of rewards and punishments given; (3) students' perceptions and attitudes towards rewards and punishments; and (4) the consistency and frequency of their application in the classroom. Thus, rewards and punishments will be more effective in improving the ability to solve academic test questions if they are applied clearly, educationally, fairly, and accompanied by continuous evaluation and consistent implementation.